Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/atmos11080782
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Urease and Nitrification Inhibitors on N2O-N Losses from Urea Fertilization to Winter Wheat in Southern Germany

Abstract: Urea (U) is the most important nitrogen (N) fertilizer in agriculture worldwide, and as N fertilizer can result in large gaseous losses of NH3 and N2O. Thus, urease inhibitors (UIs) and nitrification inhibitors (NIs) have been coupled with U fertilizers to mitigate NH3 and N2O emissions. However, it is still unclear whether adding NIs and/or UIs to U stimulates other pollutants, while reducing one pollutant. Furthermore, part of the NH3 deposition to earth is converted to N2O, leading to indirect N2O emission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Cumulative flux of N2O from wheat and rice was less than 1 kg N2O-N ha -1 during 60 days of sowing/transplanting (Table 3), out of 160 kg N ha -1 applied as urea. Many of the previous studies (Gupta et al, 2012;Aulakh et al, 2001;Hu et al, 2020) reported about similar N2O flux from wheat and rice crops. Optimum soil temperature for nitrification during wheat season (Fig 1) might be the reason for little higher N2O emission in wheat than in rice, as N2O emission is affected by many edaphic factors like soil and air temperature, moisture, N content and organic matter (Ni et al, 2014).…”
Section: Nitrous Oxide Emission In Rice and Wheatmentioning
confidence: 91%
See 2 more Smart Citations
“…Cumulative flux of N2O from wheat and rice was less than 1 kg N2O-N ha -1 during 60 days of sowing/transplanting (Table 3), out of 160 kg N ha -1 applied as urea. Many of the previous studies (Gupta et al, 2012;Aulakh et al, 2001;Hu et al, 2020) reported about similar N2O flux from wheat and rice crops. Optimum soil temperature for nitrification during wheat season (Fig 1) might be the reason for little higher N2O emission in wheat than in rice, as N2O emission is affected by many edaphic factors like soil and air temperature, moisture, N content and organic matter (Ni et al, 2014).…”
Section: Nitrous Oxide Emission In Rice and Wheatmentioning
confidence: 91%
“…As expected, and in agreement to many other reports, the use of synthetic and natural nitrification inhibitors (DCD, neem oil and pomegranate leaf extract) improved rice and wheat yields and N related traits such as percent N recovery (PNR), partial factor productivity (PFP) and N uptake in grains compared to uncoated urea (Table 4). The improved growth may be attributed to increased N availability in the form of NH4 because of slowed nitrification process (Arora and Srivastava, 2013;Hu et al, 2020;Bordoloi et al, 2020). These NH4 + cations are strongly bound to the negatively charged clay particles electrostatically and the functional groups of soil organic matter (SOM) (Zaman et al, 2013).…”
Section: Rice and Wheat Yields N Economy Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the urea fertilizers are characteristic by high risk of nitrogen loss via volatilization, which can reach 20–30% under the normal conditions [ 8 ]. Urea applied to the dry soil surface without incorporation undergoes rapid hydrolysis to ammonia form [ 9 ], and the nitrogen loss can reach more than 50%, especially during warm weather [ 10 ]. Ammonia volatilization presents a significant reduction in nitrogen fertilization efficiency, resulting in economic loss.…”
Section: Introductionmentioning
confidence: 99%
“…Urea fertilizer is the most widely used source of N for agricultural production globally (Cantarella et al., 2018; Hu et al., 2020; Pan et al., 2016), as well as in the United States (Woodley et al., 2020). Urea usage is widespread due to its low cost, high N content (46% N), and ease of transport as a stable dry‐granular substance.…”
Section: Introductionmentioning
confidence: 99%